Proposed provincial electoral districts: to accompany the Report of the Redistribution Committee 1964-65 - Lands & Surveys Branch (Producer) (Province of Ontario, 1965)
Map of proposed provincial electoral districts, created for a report of the redistribution committee for 1964-1965. Legend on the left side of the map divides cities and towns into population brackets. Geographic boundaries, railways, First Nations reserves, provincial parks, and elevations are noted in the legend. Areas highlighted in red are covered in more detail in inset maps. Scale is 1:506,880. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .